Esophageal pepsin and proton pump synthesis in barrett's esophagus and esophageal adenocarcinoma. (2nd May 2019) - Samuels, Tina L.; Altman, Kenneth W.; Gould, Jon C.; Kindel, Tammy; Bosler, Matthew; MacKinnon, Alexander; Hagen, Catherine E.; Johnston, Nikki
Abstract : Objectives/Hypothesis: Gastroesophageal reflux disease and associated metaplasia of the esophagus (Barrett's esophagus [BE]) are primary risk factors for esophageal adenocarcinoma (EAC). Widespread use of acid suppression medications has failed to stem the rise of EAC, suggesting that nonacid reflux may underlie its pathophysiology. Pepsin is a tumor promoter in the larynx and has been implicated in esophageal carcinogenesis. Herein, specimens from the esophageal cancer spectrum were tested for pepsin presence. Pepsin‐induced carcinogenic changes were assayed in an esophageal cell culture model. Study Design: Laboratory analysis. Methods: Pepsin was assayed in reflux and cancer free esophagi, BE, EAC, and esophageal cancer lacking association with reflux (squamous cell carcinoma [SCC]). Refluxed or locally synthesized pepsin was assayed by Western blot. Local synthesis of pepsin and proton pumps was assayed via reverse transcription–polymerase chain reaction. The effect of pepsin on BE and EAC markers was investigated via enzyme‐linked immunosorbent assay and quantitative polymerase chain reaction in human esophageal epithelial cells treated with pepsin or control diluent. Results: Pepsinogen and proton pump mRNA were observed in BE (3/5) and EAC (4/4) samples, but not in normal adjacent specimens, SCC (0/2), or reflux and cancer‐free esophagi. Chronic pepsin treatment (0.1–1 mg/mL, 4 weeks) of human esophageal cells in vitro induced BE and EAC markers interleukin 8 and KRT8 and depleted normal esophageal marker KRT10 ( P < .05) expression. Conclusions: Local synthesis of pepsin and proton pumps in BE and EAC is not uncommon. Absence of these molecules in normal (noncancer) esophagi, SCC, and in vitro data support a role for pepsin in reflux‐attributed carcinogenic changes in the esophagus. Level of Evidence: NA Laryngoscope, 129:2687–2695, 2019